Histochemical Staining of Acetylcholinesterase in Carnolian Honeybee (Apis mellifera carnica) Brain after Chronic Exposure to Organophosphate Diazinon - Glavan, Gordana (Journal of Apicultural Science, 2020)
Organophosphate insecticides are known to inhibit the activity of enzyme acetylcholinesterase. They affect olfactory learning and memory formation in honeybees. These insecticides cause mushroom body inactivation in honeybees, but their influence on other brain regions involved in olfactory perception and memory is unknown. The goal of this study was to study the effects of organophosphate insecticide diazinon on carnolian honeybee ( ) acetylcholinesterase activity in the olfactory brain regions of antennal lobe, mushroom body and lateral procerebrum (lateral horn). The lamina, medulla and lobula of optic lobes were also analyzed. The level of acetylcholinesterase activity was visualized using the histochemical staining method. Densitometric analysis of histochemical signals indicated that diazinon inhibited acetylcholinesterase activity only in the lip of calyces of mushroom body, but not in other analyzed olfactory regions, antennal lobe and lateral procerebrum. The visual brain system optic lobes were also unaffected. This is in accordance with the literature reporting that mushroom body is the main brain center for olfactory learning and memory formation in honeybees.